Simulation of surface crack interaction of marine solid shaft / Noor Elya Nashiewa Shabarudin and Muhammad Hussain Ismail - Shabarudin, Noor Elya Nashiewa; Ismail, Muhammad Hussain (Smart Manufacturing Research Institute (SMRI), 2023)
The marine industry relies on the transmission of power through a propeller shaft, which is typically a solid cylinder. However, when cracks appear in the shaft's hub, it is crucial to take preventative measures to avoid failure. Solid cylinders are susceptible to cracking and fracturing under various mechanical stresses, leading to single or multiple cracks. The interaction between these fractures can significantly impact the structure's collapse, and thus, this study aims to address the issues that emerge from the interaction of multiple cracks under specific loading conditions. To achieve this goal, research on various crack configurations on the cylinder's surface using finite element software, AnsysTM has been conducted to calculate the stress intensity factor (SIF) under different types of loading. The cylinder's dimensions were set to 200 mm in length and 50 mm in diameter, while the crack depth ratio ranged from 0.1 to 0.4, with an increment of 0.1. The crack aspect ratio was set to 0.6. The results were normalized to generalize the interaction factor and the relationship between two cracks and a single crack. It was found that the interaction factor is dependent on the separation distance between the cracks and the crack depth ratio. These findings suggest that preventative measures should be taken to mitigate the risks of crack formation and interaction, such as regular inspections and maintenance.